Histories on screen : the past and present in Anglo-American cinema and television - Edwards, Sam 1981- HerausgeberIn; Dolski, Michael 1978- HerausgeberIn; Sayer, Faye HerausgeberIn (Bloomsbury research skills for history, 2018)
How, as historians, should we 'read' a film? Histories on Screen answers this and other questions in a crucial volume for any history student keen to master source use. The book begins with a theoretical 'Thinking about Film' section that explores the ways in which films can be analyzed and interrogated as either primary sources, secondary sources or indeed as both. The much larger 'Using Film' segment of the book then offers engaging case studies which put this theory into practice. Topics including gender, class, race, war, propaganda, national identity and memory all receive good coverage in what is an eclectic multi-contributor volume. Documentaries, films and television from Britain and the United States are examined and there is a jargon-free emphasis on the skills and methods needed to analyze films in historical study featuring prominently throughout the text. Histories on Screen is a vital resource for all history students as it enables them to understand film as a source and empowers them with the analytical tools needed to use that knowledge in their own work